Comments on “An Empirical Assessment of the Employee Free Choice Act: the Economic Implications” by Ann Layne-Farrar - Johnson, Susan (Just Labour, 2009)
“An Empirical Assessment of the Employee Free Choice Act: The Economic Implications” by Ann Layne-Farrar provides empirical evidence concerning the impact on the U.S. unemployment rate and employment-to-population ratio should the highly controversial Employee Free Choice Act (EFCA) become law. The paper has received widespread public attention and its analysis is being used in the debate surrounding the EFCA. This commentary raises three important questions about the empirical analysis: Are the predictions presented in the study, concerning the effects of the EFCA, realistic? Is the research design likely to identify the effects of the EFCA? Why do the data used in the analysis cover such a short time period? The discussion suggests the empirical results presented in Layne-Farrar (2009) should be viewed with considerable skepticism.